The combination of MnO2@Lipo-coated gefitinib and bevacizumab inhibits the development of non-small cell lung cancer. (31st December 2022) - Zhang, Jisong; Xu, Li; Hu, Huihui; Chen, Enguo
Abstract: It can be found from a large number of cancer treatments that use of anti-cancer drugs alone often presents low efficacy and high side effects. This study aims to develop a new drug carrier with tumor-specific response, controlled release in vivo and high tumor-suppressive property. Inorganic nano-materials MnO2 with pH and glutathione (GSH, abundant in cancer cells) responsiveness were used to construct sustained-release functional nano-liposome to be an excellent in vivo pH-sensitive drug delivery system. Some hydrophilic MnO2, gefitinib (Geb), and bevacizumab (Beb) were encapsulated in the phospholipid vesicles (liposomes), so as to integrate several anti-tumor drugs (MnO2 -PDA@Lipo@Geb@Beb) to achieve effective treatment of non-small cell lung cancer (NSCLC). Part of the MnO2 nanorods on the lipid shell had the properties of pH and GSH responsiveness, which could further enhance anti-cancer efficacy. Cell assay results showed that MnO2 -PDA@Lipo@Geb@Beb nano-drug had an effective inhibition on A549 cell progression and showed excellent biocompatibility. In vivo results further confirmed that MnO2 -PDA@Lipo@Geb@Beb nano-drug could effectively inhibit the growth of NSCLC cells. Overall, it can be inferred from the above experimental results that the nanocomposite drug is expected to be widely used in the clinical application of lung cancer.